From me to you? How the UK state pension system redistributes - Rowena Crawford; Soumaya Keynes; Gemma Tetlow (Institute for Fiscal Studies (IFS), 2014)
The redistributive objectives of the UK state pension system have often been somewhat ambiguous, and have changed over time as different governments have come and gone. In this paper, we use detailed data on households' histories of employment, earnings and contributions to the National Insurance (NI) system to examine the degree of intragenerational redistribution achieved by the UK state pension system for the cohort born in the 1930s. We also estimate what redistribution could have been achieved by alternative stylised state pension systems, which approximate the steady-state version of some of the main reforms that have been implemented in the UK over the last 40 years. We find that the majority of state pension spending under all the systems we consider reflects a transfer of money across individuals' lifetimes, rather than between different individuals in the cohort. Comparisons between the different state pension systems, in terms of the extent of redistribution they imply, depend crucially on the stance taken as to whether or not individuals in couples pool their resources.
Keywords: 330